Resin compositions, cured products, composite moldings, semiconductor devices

JP7643338B2Active Publication Date: 2025-03-11MITSUBISHI CHEM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021553718
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-30
Filing Date
2020-10-30
Publication Date
2025-03-11
Estimated Expiration
2040-10-30

AI Technical Summary

Benefits of technology

【0013】 本発明の樹脂組成物によれば、熱伝導率、金属との密着性に優れ、金属と複合化した際に界面剥離しにくい硬化物が得られる。 本発明の樹脂硬化物は、熱伝導率、金属との密着性に優れ、金属と複合化した際に界面剥離しにくい。 本発明の複合成形体は、;熱伝導率、樹脂硬化物と金属との密着性に優れ、界面剥離しにくい。 本発明の半導体デバイスは、放熱性能、樹脂硬化物と金属との密着性に優れ、界面剥離しにくい。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643338000001
    Figure 0007643338000001
Patent Text Reader

Abstract

The present invention provides: a resin composition which has excellent thermal conductivity and excellent adhesion to a metal, and which enables the achievement of a cured product that is not susceptible to interfacial debonding if complexed with a metal; a cured resin which has excellent thermal conductivity and excellent adhesion to a metal, and which is not susceptible to interfacial debonding if complexed with a metal; a composite molded body which has excellent thermal conductivity and excellent adhesion to a metal, and which is not susceptible to interfacial debonding; and a semiconductor device which has excellent heat dissipation performance and excellent adhesion between a cured resin and a metal, and which is not susceptible to interfacial debonding. A resin composition according to the present invention contains an inorganic filler, a thermosetting resin an a thermosetting catalyst; the inorganic filler contains aggregated inorganic fillers; the thermosetting resin contains an epoxy resin; and two or more thermosetting catalysts having a melting point of 100°C or higher are contained. A cured resin according to the present invention is a cured product of the above-described resin composition; a composite body according to the present invention comprises the above-described cured resin and a metal; and a semiconductor device according to the present invention comprises the above-described composite body.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a cured product, a composite molded article, and a semiconductor device. This application claims priority based on Japanese Patent Application No. 2019-197273, filed on October 30, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] Power semiconductor devices are used in various fields such as railways, automobiles, general home appliances, etc. In recent years, power semiconductor devices are shifting from conventional power semiconductors using Si to power semiconductors using SiC, AlN, GaN, etc. in order to achieve further miniaturization, cost reduction, and efficiency improvement. Power semiconductor devices are generally used as power semiconductor modules in which a plurality of semiconductor devices are arranged on a common heat sink and packaged.

[0003] Various issues have been pointed out for the practical application of such power semiconductor devices, one of which is the problem of dissipating heat generated by the devices. Generally, power semiconductor devices can achieve high output and high density by operating at high temperatures, so insufficient heat dissipation affects the reliability of the power semiconductor devices. For example, there is concern that heat generated by switching of the devices will reduce reliability. In particular, in recent years, the density of integrated circuits has been increasing further in the electrical and electronic fields, and the heat generated by such increases in density has become an urgent issue.

[0004] One method to solve this problem is to use highly thermally conductive ceramic substrates such as alumina substrates and aluminum nitride substrates as heat dissipation substrates on which power semiconductor devices are mounted. However, ceramic substrates have drawbacks such as being easily cracked by impact, and being difficult to make thin and compact.

[0005] In view of this, a heat dissipating resin sheet using an inorganic filler-containing resin composition containing a thermosetting resin such as a highly thermally conductive epoxy resin and a highly thermally conductive inorganic filler has been proposed (for example, Patent Document 1). Patent Document 1 describes a heat dissipating resin sheet containing a resin and a boron nitride filler, in which the content of the boron nitride filler is 30 vol% or more and 60 vol% or less, and the Tg of the resin is 60°C or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-36415 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, when a conventional heat dissipating resin sheet using an inorganic filler-containing resin composition is applied to a power semiconductor device, the following problems (1) to (3) arise.

[0008] (1) When incorporating a heat dissipating resin sheet into a power semiconductor device, a molding and pressurizing process is performed in which pressure is applied to the resin composition to bond the resin composition to a metal and harden it. However, if the resin composition is produced and then stored, and the molding and pressurizing process is performed after the storage period has elapsed, the longer the storage period, the more the curing reaction of the thermosetting resin in the resin composition progresses, and the resin composition may not be able to exhibit its original performance in the molding process. For example, if the curing reaction of the thermosetting resin progresses too much, the adhesion of the heat dissipating resin sheet to the metal decreases.

[0009] (2) In addition, as a method for improving the thermal conductivity in the thickness direction of the heat dissipating resin sheet, pressure is applied to the resin composition in the molding and pressurizing process to cause the inorganic fillers in the resin composition to adhere to each other. However, if the curing reaction of the thermosetting resin proceeds too much during storage of the resin composition, the inorganic fillers will not adhere to each other even if pressure is applied in the molding and pressurizing process. As a result, it becomes difficult to sufficiently improve the thermal conductivity of the heat dissipating resin sheet. In order to achieve high thermal conductivity, for example, an aggregated inorganic filler that is easily deformed by a molding and pressurizing process can be used. However, if the curing reaction of the thermosetting resin proceeds too much during storage of the resin composition, the deformation of the aggregated inorganic filler is also inhibited, and the effect of improving the thermal conductivity due to the improved adhesion between the inorganic fillers is also inhibited.

[0010] (3) Furthermore, as a method for improving the insulation properties and adhesion to metals of heat dissipation resin sheets, pressure is applied to the resin composition in the molding and pressurizing process to remove voids within the resin composition and at the interface between the resin composition and the metal. However, if the curing reaction of the thermosetting resin progresses too much during storage of the resin composition, it becomes difficult to remove the voids in the molding and pressurizing process. If the voids are not sufficiently removed, the cured product and the metal may peel off at the interface during heating in a reflow furnace in the manufacturing process of the power semiconductor module.

[0011] The present invention provides: a resin composition which gives a cured product which has excellent thermal conductivity and adhesion to metals and which is resistant to interfacial delamination when composited with metal; a cured resin product which has excellent thermal conductivity and adhesion to metals and which is resistant to interfacial delamination when composited with metal; a composite molded product which has excellent thermal conductivity and adhesion between the cured resin product and metal and which is resistant to interfacial delamination; and a semiconductor device which has excellent heat dissipation performance and adhesion between the cured resin product and metal and which is resistant to interfacial delamination. [Means for solving the problem]

[0012] [1] A resin composition containing an inorganic filler, a thermosetting resin, and a thermosetting catalyst, wherein the inorganic filler contains an aggregated inorganic filler, the thermosetting resin contains an epoxy resin, and the resin composition contains two or more types of thermosetting catalysts having a melting point of 100°C or higher. [2] The resin composition according to [1], wherein at least one of the thermosetting catalysts has a structure derived from imidazole. [3] The resin composition according to [2], wherein the thermosetting catalyst having a structure derived from imidazole further has a structure derived from triazine in one molecule. [4] The resin composition according to any one of [1] to [3], wherein two or more of the thermosetting catalysts have a structure derived from imidazole. [5] The resin composition according to any one of [1] to [4], wherein at least one of the thermosetting catalysts has a melting point of 200° C. or higher. [6] The resin composition according to any one of [1] to [5], wherein the resin composition optionally further contains a solvent, and the content of the thermosetting catalyst is 0.1 to 10 mass% relative to 100 mass% of the resin composition excluding the inorganic filler and the optionally contained solvent. [7] The resin composition according to any one of [1] to [6], wherein the solubility of the thermosetting catalyst in N,N-dimethylformamide at 25° C. is 10 mass % or less. [8] The resin composition according to any one of [1] to [7], wherein the agglomerated inorganic filler contains agglomerated particles of boron nitride. [9] The resin composition according to any one of [1] to [8], further comprising alumina.

[10] The resin composition according to any one of [1] to [9], wherein the agglomerated inorganic filler is boron nitride agglomerated particles having a house-of-cards structure.

[11] The resin composition according to any one of [1] to

[10] , wherein the main component of the resin composition is an epoxy resin.

[12] A cured resin product using the resin composition according to any one of [1] to

[11] .

[13] A composite molded article having the resin cured product according to

[12] and a metal.

[14]

[13] A semiconductor device having a composite molding. Effect of the Invention

[0013] The resin composition of the present invention gives a cured product which has excellent thermal conductivity and adhesion to metals and is resistant to interfacial peeling when composited with a metal. The cured resin of the present invention has excellent thermal conductivity and adhesion to metals, and is resistant to interfacial peeling when combined with a metal. The composite molded product of the present invention has excellent thermal conductivity and adhesion between the cured resin and metal, and is resistant to interfacial peeling. The semiconductor device of the present invention has excellent heat dissipation properties and excellent adhesion between the cured resin and metal, and is resistant to interfacial peeling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following describes in detail the embodiments of the present invention, but the present invention is not limited to the following embodiments and can be modified in various ways within the scope of the invention.

[0015] <Resin composition> The resin composition of the present invention includes an aggregated inorganic filler, a thermosetting resin, and a thermosetting catalyst. The resin composition of the present invention is a composition in a state before curing. For example, a slurry-like resin composition to be subjected to a coating process described later, a sheet that has been subjected to a coating process, a sheet that has been subjected to a process such as coating and drying, and other compositions in a state before curing are all treated as resin compositions. On the other hand, a cured resin product using the resin composition of the present invention has an exothermic peak of 10 J / g or less when heated from 40°C to 250°C at a rate of 10°C / min in DSC (differential scanning calorimetry).

[0016] In the resin composition of the present invention, the thermosetting resin contains an epoxy resin, and the thermosetting catalyst contains two or more types of thermosetting catalysts having a melting point of 100° C. or higher. Therefore, the reaction rate of the thermosetting resin can be reduced, and excessive progress of the curing reaction can be suppressed. Here, it is possible to reduce the amount of the curing catalyst in order to slow down the reaction rate and inhibit the progress of the curing reaction. However, if the amount of the curing catalyst is reduced, the curing reaction of the thermosetting resin stops midway or the curing reaction progresses insufficiently. As a result, the elastic modulus of the cured product decreases, and the thermal conductivity, strength, dielectric properties, heat resistance, etc. of the cured product decrease. Therefore, in the present invention, by combining two or more different thermosetting catalysts each having a melting point of 100° C. or more, the reaction rate of the thermosetting resin during storage can be reduced, and the curing reaction can be sufficiently advanced when curing in a molding and pressurizing process, etc. Such a resin composition can be suitably used as a material for a heat dissipation sheet for a power semiconductor device, and a highly reliable power semiconductor module can be realized.

[0017] (Inorganic filler) The resin composition of the present invention contains an inorganic filler. The inorganic filler contains an aggregated inorganic filler. The inorganic filler may further contain non-aggregated inorganic filler in addition to the aggregated inorganic filler. However, in order to improve the thermal conductivity and control the linear expansion coefficient of the cured resin of the present invention, it is preferable to increase the proportion of the aggregated inorganic filler in the inorganic filler. Since the resin composition of the present invention contains aggregated inorganic fillers in the inorganic filler, the aggregated inorganic fillers are easily deformed and come into surface contact with each other during the molding and pressurizing process. Therefore, more paths for heat conduction are formed, and the thermal conductivity of the cured product tends to be high. The aggregated morphology of the aggregated inorganic fillers can be confirmed by a scanning electron microscope (SEM). The resin composition of the present invention may contain, in addition to the inorganic filler, a non-aggregated inorganic filler and an organic filler in combination.

[0018] The aggregated inorganic filler is preferably an electrically insulating inorganic compound, for example, a filler composed of particles of at least one type selected from the group consisting of metal carbides, metal oxides, and metal nitrides. Examples of metal carbides include silicon carbide, titanium carbide, and tungsten carbide. Examples of metal oxides include magnesium oxide, aluminum oxide, silicon oxide, calcium oxide, zinc oxide, yttrium oxide, zirconium oxide, cerium oxide, ytterbium oxide, and sialon (ceramics made of silicon, aluminum, oxygen, and nitrogen). Examples of metal nitrides include boron nitride, aluminum nitride, and silicon nitride. Among these, metal oxides and metal nitrides are preferred because the cured resin has excellent electrical insulation properties.

[0019] Since power semiconductors require insulation, it is preferable that the aggregated inorganic filler is made of an inorganic compound with excellent insulation properties. 13 Inorganic compounds with a volume resistivity of 1×10 Ω·cm or more are preferred. 14 Inorganic compounds with a resistance of Ω·cm or more are more preferable. An example of an inorganic compound with excellent insulating properties is alumina (Al2O3, volume resistivity: 1×10 14 Ω cm), Aluminum Nitride (AlN, volume resistivity: 1×10 14 Ω cm), Boron nitride (BN, volume resistivity: 1×10 14 Ω·cm), silicon nitride (Si3N4, volume resistivity 1×10 14 Ω cm), silica (SiO2, volume resistivity 1×10 14 Ω·cm) etc. Among these, alumina, aluminum nitride, boron nitride, and silica are preferable, and alumina and boron nitride are more preferable.

[0020] The aggregated inorganic filler may be surface-treated with a surface treatment agent. As the surface treatment agent, a known surface treatment agent can be used.

[0021] The aggregated inorganic filler may be used alone or in any combination and ratio of two or more kinds.

[0022] The method and degree of aggregation of the aggregated inorganic filler are not particularly limited. However, it is preferable to use the following boron nitride aggregated particles as the aggregated inorganic filler. In addition, the boron nitride aggregated particles may be used in combination with a filler of a different shape and type.

[0023] [Boron nitride agglomerated particles] Boron nitride has high thermal conductivity, but is flaky, and while it conducts heat in the planar direction, it has high thermal resistance in the direction perpendicular to the planar direction. In order to improve handling, it is preferable to use agglomerated particles made by gathering the flakes and agglomerating them into a spherical shape.

[0024] The boron nitride agglomerated particles preferably have a house-of-cards structure. The "house of cards structure" is described, for example, in Ceramics 43 No. 2 (published by the Ceramic Society of Japan in 2008), and is a structure in which plate-shaped particles are layered in a complex manner without being oriented. More specifically, boron nitride agglomerated particles having a house-of-cards structure are aggregates of boron nitride primary particles, in which the flat surfaces and end surfaces of the primary particles come into contact with each other to form, for example, a T-shaped aggregate. As the boron nitride agglomerated particles used in the present invention, boron nitride agglomerated particles having the above-mentioned house-of-card structure are particularly preferred, and by using boron nitride agglomerated particles having a house-of-card structure, the thermal conductivity can be further increased.

[0025] The new Mohs hardness of the boron nitride agglomerated particles is not particularly limited, but is preferably 5 or less. When the new Mohs hardness is 5 or less, the particles dispersed in the resin composition tend to come into surface contact with each other, forming a heat conduction path between the particles, and the heat conduction of the cured resin tends to be improved. The lower limit of the new Mohs hardness is not particularly limited, but is, for example, 1 or more.

[0026] The volume average particle size of the boron nitride agglomerated particles is not particularly limited, but is preferably 10 μm or more, more preferably 15 μm or more. If the volume average particle size is equal to or more than the lower limit, the number of particles in the resin composition and the cured product using the resin composition is relatively small, and the number of interparticle interfaces is reduced, resulting in a low thermal resistance and a high thermal conductivity of the composite resin sheet. The volume average particle diameter of the boron nitride agglomerated particles is preferably 100 μm or less, and more preferably 90 μm or less. When the volume average particle diameter is equal to or less than the upper limit, the surface smoothness of the cured product using the resin composition tends to be obtained.

[0027] Here, the volume average particle size of boron nitride agglomerated particles means the particle size at which the cumulative volume is 50% when a cumulative curve is drawn with the volume of the powder used for measurement being 100%. The measurement method includes a wet measurement method in which a sample in which agglomerated particles are dispersed in a pure water medium containing sodium hexametaphosphate as a dispersion stabilizer is measured using a laser diffraction / scattering type particle size distribution measuring device, and a dry measurement method in which a "Morphologi" manufactured by Malvern is used for measurement. The same applies to the spherical filler described below.

[0028] [Content of aggregated inorganic filler] The content of the aggregated inorganic filler in the resin composition of the present invention is preferably 20% by mass or more, more preferably 30% by mass or more, more preferably 40% by mass or more, and particularly preferably 50% by mass or more, based on 100% by mass of the resin composition. The content of the aggregated inorganic filler in the resin composition of the present invention is preferably 99% by mass or less, more preferably 90% by mass or less, and particularly preferably 80% by mass or less, based on 100% by mass of the resin composition. In addition, the combination of the upper limit and lower limit of the content of the aggregated inorganic filler is not particularly limited, but is preferably 20% by mass or more and 99% by mass or less, more preferably 30% by mass or more and 99% by mass or less, more preferably 40% by mass or more and 90% by mass or less, and particularly preferably 50% by mass or more and 80% by mass or less. When the content of the aggregated inorganic filler is equal to or more than the lower limit, the effect of improving thermal conductivity and the effect of controlling the linear expansion coefficient due to the inclusion of the aggregated inorganic filler tend to be sufficiently obtained, while when the content of the aggregated inorganic filler is equal to or less than the upper limit, the moldability of the resin cured product and the interfacial adhesion in the composite molded product tend to be improved.

[0029] When other non-agglomerated inorganic fillers are used in addition to the agglomerated inorganic filler, the content ratio of the agglomerated inorganic filler to the other non-agglomerated inorganic fillers in the resin composition is not particularly limited, but is preferably 90:10 to 10:90 in mass ratio, and more preferably 80:20 to 20:80.

[0030] [Breaking strength of aggregated inorganic filler] The breaking strength of the aggregated inorganic filler is not particularly limited, but is preferably 300 MPa or less, more preferably 100 MPa or less, even more preferably 50 MPa or less, even more preferably 20 MPa or less, particularly preferably 15 MPa or less, and most preferably 10 MPa or less. If the breaking strength is below the upper limit, the aggregated structure of the aggregated inorganic filler is deformed when pressed, and the aggregated inorganic filler particles are likely to come into surface contact with each other. On the other hand, the lower limit of the breaking strength is not particularly limited, but from the viewpoint of easy handling, the breaking strength is preferably 2.5 MPa or more, more preferably 3 MPa or more, even more preferably 3.5 MPa or more, and particularly preferably 4 MPa or more. When the fracture strength of the aggregated inorganic filler is within the above range, the aggregated inorganic filler tends to deform at the contacting portion and to easily come into surface contact with each other. While maintaining a high thermal conductivity inside the aggregated inorganic filler, the contact thermal resistance at the interface between the aggregated inorganic filler and the interface between the metal substrate and the heat dissipation sheet described later can be reduced, and the overall thermal conductivity can be improved.

[0031] [Elastic modulus of aggregated inorganic filler] The elastic modulus of the aggregated inorganic filler is not particularly limited, but is preferably 10 MPa or more, more preferably 20 MPa or more, even more preferably 30 MPa or more, particularly preferably 50 MPa or more, and most preferably 55 MPa or more. If the elastic modulus is above the lower limit, the aggregated inorganic filler tends to plastically deform in the direction of the pressing pressure, and the collapse of the aggregated structure can be suppressed. On the other hand, the upper limit of the elastic modulus is not particularly limited, but from the viewpoint of easily obtaining sufficient deformation, it is preferably 5 GPa or less, more preferably 2 GPa or less, even more preferably 1.5 GPa or less, even more preferably 1 GPa or less, even more preferably 500 MPa or less, particularly preferably 300 MPa or less, and most preferably 150 MPa or less. When the elastic modulus of the aggregated inorganic filler is within the above range, the aggregated inorganic filler tends to easily maintain its spherical shape during press processing.

[0032] When the agglomerated inorganic filler is present in a heat dissipation sheet, the breaking strength and elastic modulus of the agglomerated inorganic filler can be measured after baking the resin of the heat dissipation sheet and removing the agglomerated inorganic filler so as not to alter the agglomerated inorganic filler.

[0033] [Other non-agglomerated inorganic fillers] In addition to the aggregated inorganic filler, other non-aggregated inorganic fillers may be used in combination. As the other non-aggregated inorganic fillers, for example, spherical fillers can be mentioned in addition to those mentioned above. The other non-aggregated fillers are not limited to spherical fillers. For example, other non-aggregated fillers include scaly boron nitride primary particles and the like, and are not limited to spherical fillers.

[0034] The thermal conductivity of the spherical filler is preferably 10 W / m·K or more, more preferably 15 W / m·K or more, and even more preferably 20 W / m·K or more. The thermal conductivity of the spherical filler is preferably, for example, 10 to 30 W / m·K. The new Mohs hardness of the spherical filler is preferably 3.1 or more. The new Mohs hardness of the spherical filler is preferably, for example, 5 to 10. By using such a spherical filler in combination with the above-mentioned aggregated inorganic filler, the adhesive strength to metal and heat dissipation properties of the obtained resin cured product can be improved.

[0035] Here, "spherical" refers to anything that is generally recognized as being spherical, and for example, an average circularity of 0.4 or more may be considered spherical, and an average circularity of 0.6 or more may be considered spherical. Usually, the upper limit of the average circularity is 1. The circularity can be measured by subjecting the projected image to image processing, and can be measured, for example, with Sysmex Corporation's FPIA series.

[0036] The spherical filler is preferably at least one selected from the group consisting of alumina, synthetic magnesite, crystalline silica, aluminum nitride, silicon nitride, silicon carbide, zinc oxide, and magnesium oxide. By using these preferable spherical fillers, the heat dissipation properties of the obtained resin cured product can be further improved.

[0037] The average particle size of the spherical filler is preferably 0.5 μm or more and 40 μm or less. When the average particle size is 0.5 μm or more, the resin and the filler can easily flow during hot molding, and it is considered that the interfacial adhesive strength of the composite molded product of the present invention can be increased. Also, when the average particle size is 40 μm or less, the dielectric breakdown properties of the cured resin are easily maintained.

[0038] There is no limitation on the shape of the inorganic filler, and it may be in the form of particles, whiskers, fibers, plates, or aggregates thereof.

[0039] [Organic filler] In addition to the aggregated inorganic filler, an organic filler may be used in combination. In the present invention, the organic filler is a component that does not contain an epoxy group, does not fall under the category of a thermosetting catalyst, and is solid at room temperature, composed of organic components. Examples of the organic filler include natural products such as wood flour, cellulose that may be modified, starch, various organic pigments, thermoplastic resins, and thermosetting resins. Specific examples include acrylic resin particles, nylon resin particles, polyester resin particles, polystyrene resin particles, and silicone resin particles. These may be used alone or in combination of two or more types. When an organic filler is contained, it may be possible to impart appropriate elongation to the resin composition, reduce the stress generated, and suppress the occurrence of cracks during a temperature cycle test.

[0040] The upper limit of the average particle size of the organic filler is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. When the average particle size of the organic filler is equal to or less than the upper limit, the risk of a decrease in thermal conductivity can be reduced when producing heat dissipation insulation sheets of various thicknesses. The particle size of the organic filler is also an average particle size determined from the volume average particle size distribution measurement results measured by a laser diffraction particle size distribution measurement device.

[0041] (thermosetting resin) The thermosetting resin contained in the resin composition of the present invention is not particularly limited as long as it can be cured in the presence of a curing agent and a curing catalyst to give a cured product. Specific examples of the thermosetting resin include epoxy resin, phenol resin, polycarbonate resin, unsaturated polyester resin, urethane resin, melamine resin, and urea resin. Among these, epoxy resin is preferred from the viewpoints of viscosity, heat resistance, moisture absorption, and handling. Examples of the epoxy resin include epoxy group-containing silicon compounds, aliphatic epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, novolac epoxy resins, alicyclic epoxy resins, glycidyl ester epoxy resins, multifunctional epoxy resins, and polymeric epoxy resins.

[0042] [Epoxy resin] Epoxy resin is a general term for compounds that have one or more oxirane rings (epoxy groups) in the molecule. The oxirane rings (epoxy groups) contained in the epoxy resin may be either alicyclic epoxy groups or glycidyl groups, but glycidyl groups are more preferred from the viewpoints of reaction speed and heat resistance.

[0043] The epoxy resin used in the present invention may be an aromatic oxirane ring (epoxy group)-containing compound. Specific examples thereof include bisphenol-type epoxy resins obtained by glycidylating bisphenols such as bisphenol A, bisphenol F, bisphenol AD, bisphenol S, tetramethyl bisphenol A, tetramethyl bisphenol F, tetramethyl bisphenol AD, tetramethyl bisphenol S, and tetrafluorobisphenol A; biphenyl-type epoxy resins, dihydroxynaphthalene, and 9,9-bis(4-hydroxyphenyl)fluorene; glycidylating trisphenols such as 1,1,1-tris(4-hydroxyphenyl)methane; glycidylating tetrakisphenols such as 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane; novolac-type epoxy resins obtained by glycidylating novolacs such as phenol novolac, cresol novolac, bisphenol A, novolac, and brominated bisphenol A novolac; and the like.

[0044] The epoxy resin contained in the resin composition of the present invention is not particularly limited, but is preferably at least one or more selected from the group consisting of various bisphenol-type epoxy resins obtained by glycidylating bisphenols, such as bisphenol A-type epoxy resins and bisphenol F-type epoxy resins; various biphenyl-type epoxy resins obtained by glycidylating biphenyls, epoxy resins obtained by glycidylating aromatic compounds having two hydroxyl groups, such as dihydroxynaphthalene and 9,9-bis(4-hydroxyphenyl)fluorene; epoxy resins obtained by glycidylating trisphenols, such as 1,1,1-tris(4-hydroxyphenyl)methane, and epoxy resins obtained by glycidylating tetrakisphenols, such as 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane; novolac-type epoxy resins obtained by glycidylating novolacs, such as phenol novolac, cresol novolac, bisphenol A novolac, and brominated bisphenol A novolac; and silicone-containing epoxy resins.

[0045] The epoxy resin used in the present invention preferably contains a polyfunctional epoxy resin, which is an epoxy resin having three or more oxirane rings (epoxy groups) per molecule.

[0046] From the viewpoint of increasing the storage modulus of the cured resin of the present invention, particularly the storage modulus at high temperatures, an epoxy resin having two or more oxirane rings (epoxy groups) in the molecule is preferred, an epoxy resin having three or more oxirane rings (epoxy groups) in the molecule is more preferred, and an epoxy resin having four or more glycidyl groups in the molecule is even more preferred. The storage modulus at high temperatures of the cured resin becomes important when the amount of heat generated is large, such as in a power semiconductor. By having multiple oxirane rings (epoxy groups), especially glycidyl groups, in the molecule, the crosslink density of the cured product is improved, and the resulting cured resin product has higher strength. Therefore, when internal stress occurs in the cured resin product during a moisture absorption reflow test, the cured resin product does not deform or break, but maintains its shape, thereby preventing the generation of voids and other spaces in the cured resin product. From the viewpoint of increasing the storage modulus of the cured resin, the molecular weight of the polyfunctional epoxy resin is preferably 1,000 or less, and more preferably 800 or less. The lower limit of the molecular weight of the polyfunctional epoxy resin is not particularly limited, but is, for example, 100 or more.

[0047] By adding a multifunctional epoxy resin, it is possible to introduce highly polar oxirane rings (epoxy groups) at a high density, which increases the effects of physical interactions such as van der Waals forces and hydrogen bonds, improving the adhesion between the metal and the cured resin in the composite molded product. In addition, the addition of a polyfunctional epoxy resin can increase the storage modulus of the cured resin after thermal curing, so that after the cured resin of the resin composition penetrates into the irregularities of the metal to be adhered, a strong anchor effect is exhibited, improving the adhesion between the metal and the cured resin.

[0048] On the other hand, the introduction of a polyfunctional epoxy resin tends to increase the hygroscopicity of the resin composition, but by improving the reactivity of the oxirane ring (epoxy group), the amount of hydroxyl groups during the reaction can be reduced and the increase in hygroscopicity can be suppressed. In addition, by combining the above-mentioned epoxy resin and a polyfunctional epoxy resin to produce a resin composition, it is possible to achieve both high elasticity and low hygroscopicity of the resin cured product.

[0049] Specifically, the polyfunctional epoxy resin is preferably an epoxy resin having three or more epoxy groups, and for example, EX321L, DLC301, DLC402 manufactured by Nagase ChemteX Corporation, BATG, PETG manufactured by Showa Denko KK, and the like can be used. These polyfunctional epoxy resins may be used alone or in combination of two or more.

[0050] [Thermosetting resin content] When the resin composition of the present invention further contains a solvent, the content of the thermosetting resin in the resin composition is preferably 5 to 90% by mass, more preferably 10 to 60% by mass, based on 100% by mass of the resin composition excluding the inorganic filler and the solvent. When the content of the thermosetting resin is equal to or more than the lower limit, the moldability is good. When the content of the thermosetting resin is equal to or less than the upper limit, the content of other components can be secured, and the thermal conductivity can be increased.

[0051] Furthermore, when the solvent, inorganic filler and thermosetting catalyst are excluded from the resin composition of the present invention, the main component is preferably an epoxy resin. Here, the main component refers to the component that is present in the largest amount. The proportion of the epoxy resin in the resin composition excluding the inorganic filler and the thermosetting catalyst is not particularly limited, but is preferably 20% by mass or more, and more preferably 45% by mass or more. The upper limit of the proportion of the epoxy resin is 100 mass %, and the entire composition may be epoxy resin. The proportion of the epoxy resin within the above range tends to provide low moisture absorption, high elastic modulus, high toughness, easy reaction control, high reflow resistance, high reliability in cycle tests, and high thermal conductivity.

[0052] The resin composition of the present invention preferably contains 5% by mass or more, more preferably 10% by mass or more, of the polyfunctional epoxy resin, which is the above-mentioned preferred epoxy resin, in the total epoxy resin. The resin composition of the present invention also preferably contains 50% by mass or less, more preferably 40% by mass or less, of the polyfunctional epoxy resin in the total epoxy resin. When the content of the polyfunctional epoxy resin is equal to or more than the lower limit, the above-mentioned effect due to the inclusion of the polyfunctional epoxy resin can be effectively obtained. On the other hand, when the content of the polyfunctional epoxy resin is equal to or less than the upper limit, the moisture absorption of the cured product is suppressed and the strength performance of the cured product is excellent, and it is possible to achieve both of these.

[0053] From the viewpoints of film-forming property, low moisture absorption, and flexibility, it is more preferable that the epoxy resin used in the present invention contains a high molecular weight epoxy resin. Specifically, the high molecular weight epoxy resin is preferably an epoxy resin having a mass average molecular weight of 10,000 or more, more preferably an epoxy resin having a mass average molecular weight of 20,000 or more, and particularly preferably an epoxy resin having a mass average molecular weight of 30,000 or more. Moreover, the high molecular weight epoxy resin is preferably an epoxy resin having a mass average molecular weight of 100,000 or less, and even more preferably an epoxy resin having a mass average molecular weight of 80,000 or less. High molecular weight epoxy resins are preferably more hydrophobic. Specifically, they are preferably 5,000 g / equivalent or more, more preferably 7,000 g / equivalent or more, and more preferably 20,000 g / equivalent or less.

[0054] Here, the mass average molecular weight of the epoxy resin is a value calculated in terms of polystyrene measured by gel permeation chromatography. The epoxy equivalent is defined as "the mass of the epoxy resin containing one equivalent of epoxy groups" and can be measured in accordance with JIS K7236.

[0055] Such high molecular weight epoxy resins may be used alone or in combination of two or more. Other epoxy resins that are not high molecular weight may also be used in combination.

[0056] (Thermosetting catalyst) The resin composition of the present invention contains two or more thermosetting catalysts having a melting point of 100° C. or higher. By using these thermosetting catalysts, the reaction rate of the thermosetting resin during storage can be reduced. Furthermore, when the resin composition is cured in a molding and pressurizing process, the curing reaction can be sufficiently promoted. When the resin composition contains only one type of thermosetting catalyst, it is difficult to obtain the effect of the present invention. For example, if the amount of a single thermosetting catalyst is increased too much in order to increase the reaction rate, the storage stability of the resin composition may deteriorate. In addition, the increase in reaction rate inhibits the deformation and contact of the inorganic filler when pressurized, so that the cured resin tends not to have a high thermal conductivity. On the other hand, if the amount of a single thermosetting catalyst is reduced too much, the curing rate slows down, and as a result, the resin composition is poorly cured, resulting in a cured resin with a low elastic modulus and high moisture absorption. Therefore, in the moisture absorption reflow test, the interface between the metal and the cured resin tends to peel off, or the voids in the cured resin tend to expand and the insulation property deteriorates. Therefore, it is important to use two or more types of thermosetting catalysts with a melting point of 100 ° C or more in combination so that the final cured product does not become poorly cured while controlling the curing rate when pressurized.

[0057] The thermosetting catalyst is not particularly limited as long as two or more thermosetting catalysts having a melting point of 100° C. or higher are used. Furthermore, it is preferable that at least one of the melting points is 200° C. or higher, and it is more preferable that two or more of the melting points are 200° C. or higher. When the melting point of one or more of the catalysts is 200° C. or higher, the reaction rate of the thermosetting resin during storage can be further reduced, which is more preferable from the viewpoint of storage stability. The difference (absolute value) in the melting points of two or more thermosetting catalysts is not particularly limited, but is preferably 100° C. or less, more preferably 80° C. or less, and more preferably 5° C. or more. By keeping it within these ranges, the reaction rate of the thermosetting resin during storage can be reduced, and further, when curing is performed in a molding and pressurizing process or the like, the curing reaction tends to proceed sufficiently.

[0058] Examples of the thermosetting catalyst having a melting point of 100° C. or more include imidazole compounds, linear or cyclic tertiary amines, organic phosphorus compounds, quaternary phosphonium salts, diazabicycloalkenes such as organic acid salts, etc. Also usable are organometallic compounds, quaternary ammonium salts, metal halides, etc. Examples of the organometallic compounds include zinc octylate, tin octylate, and aluminum acetylacetone complexes.

[0059] From the viewpoint of enhancing the effect of improving the adhesion between the cured resin of the present invention and metal, it is preferable that at least one of the thermosetting catalysts has a structure derived from imidazole, and it is more preferable that two or more of the thermosetting catalysts have a structure derived from imidazole. In addition, in order to improve adhesion and suppress peeling after reflow, it is preferable that the thermosetting catalyst further has a structure derived from triazine. In particular, it is preferable from the viewpoint of adhesion that at least one of the thermosetting catalysts having a structure derived from imidazole further has a structure derived from triazine in one molecule. Two or more thermosetting catalysts may have a structure derived from imidazole and a structure derived from triazine in one molecule. By using these structures, the structure derived from triazine acts with the metal through hydrogen bonding or the like to improve adhesion, and at the same time, epoxy polymerization begins from the structure derived from imidazole in the same molecule, so that the adhesion between the resin cured product and the metal tends to be further improved.

[0060] Examples of preferred imidazole compounds and triazine compounds having a melting point of 100° C. or higher include 2,4-diamino-6-[2′-ethyl-4′-methylimidazolyl-(17′)]-ethyl-s-triazine, 2-phenyl-4,5-dihydroxymethylimidazole, 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 2,4-diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s-triazine, 2, Examples of the compound include 4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole.

[0061] Among these, the structure derived from imidazole and the structure derived from triazine are particularly preferred, and the structure derived from triazine is particularly preferred, and as the triazine, the structure derived from 1,3,5-triazine is particularly preferred. In addition, the structure may have a plurality of structural parts exemplified by these. These structures have high compatibility with thermosetting resins and high reaction activation temperatures, so that the curing speed and physical properties after curing can be easily adjusted. Therefore, there is a tendency to realize improved storage stability of the resin composition and further improved adhesive strength after heat molding.

[0062] [Thermosetting catalyst content] The content of the thermosetting catalyst is preferably 0.1 to 10% by mass, more preferably 0.1 to 5% by mass, and even more preferably 0.5 to 4% by mass, based on 100% by mass of the resin composition of the present invention excluding the solvent and inorganic filler. When the content of the curing catalyst is equal to or more than the lower limit, the progress of the curing reaction can be sufficiently promoted to achieve good curing. When the content of the curing catalyst is equal to or less than the upper limit, the curing speed does not become too fast. Therefore, when the content of the thermosetting catalyst is within the above numerical range, the storage stability of the resin composition of the present invention can be improved, the thermal conductivity of the cured product can be improved, and the insulation can be improved by efficiently removing voids in the cured product. Here, the solvent is not an essential component in the resin composition of the present invention, that is, the resin composition of the present invention may or may not contain a solvent. When the resin composition of the present invention contains a solvent, the content of the thermosetting catalyst is expressed as a ratio (mass %) to the amount excluding the solvent and inorganic filler from the total amount of the resin composition. When the resin composition of the present invention does not contain a solvent, the content of the thermosetting catalyst is expressed as a ratio (mass %) to the total amount of the resin composition excluding the inorganic filler.

[0063] The content of the thermosetting catalyst having both triazine-derived structures in one molecule is preferably 0.01 to 5 mass%, more preferably 0.15 to 5 mass%, and even more preferably 0.2 to 4 mass%, based on 100 mass% of the resin composition excluding the inorganic filler and the solvent. By being in these ranges, the adhesion to a copper plate or the like tends to be improved. Furthermore, the content of the thermosetting catalyst having both a structure derived from imidazole and a structure derived from triazine in one molecule is preferably 0.1 to 5% by mass, more preferably 0.5 to 4% by mass, and even more preferably 0.7 to 3% by mass, based on 100% by mass of the resin composition excluding the inorganic filler and the solvent. If these contents are equal to or greater than the lower limit, the progress of the curing reaction can be sufficiently promoted to achieve good curing. If the content of the thermosetting catalyst having both a structure derived from imidazole and a structure derived from triazine in one molecule is equal to or less than the upper limit, the curing speed is not too fast, and therefore the storage stability of the resin composition of the present invention is improved, the thermal conductivity of the cured product is improved, and the insulation is improved by efficiently removing voids in the cured product.

[0064] The average particle size of the thermosetting catalyst is not particularly limited, but the average particle size of at least one thermosetting catalyst is preferably 15 μm or less, more preferably 10 μm or less. The average particle size of at least one thermosetting catalyst is preferably 50 nm or more, more preferably 100 nm or more, even more preferably 500 nm or more, and even more preferably 1000 nm or more. When the average particle size is below the upper limit, the solubility of the thermosetting catalyst in the resin component tends to improve, and the reaction rate tends to improve. In addition, the elastic modulus of the resin cured product can be made higher, and the glass transition temperature tends to be increased. In addition, the dispersibility of the thermosetting catalyst tends to improve, and the storage stability tends to improve. On the other hand, when the average particle size is equal to or larger than the lower limit, secondary aggregation of the thermosetting catalyst itself is suppressed, dispersibility of the thermosetting catalyst is improved, and storage stability of the resin composition tends to be improved. In addition, handling properties during production of the resin composition also tend to be good. The average particle size of the multiple thermosetting catalysts is not particularly limited, but the average particle size of the multiple thermosetting catalysts may be in the above range.

[0065] At least one of the thermosetting catalysts of the present invention preferably has a solubility in N,N-dimethylformamide (DMF) at 25° C. of 10% by mass or less, more preferably 8% by mass or less. The lower limit of the solubility in DMF is not particularly limited, but may be, for example, 0.01% by mass or less. In addition, it is particularly preferable that the solubility of two or more thermosetting catalysts in DMF is 10% by mass or less. Since DMF is a highly polar solvent, the reaction of the thermosetting catalyst is inhibited by the insolubility of the thermosetting catalyst in DMF, and the storage stability of the resin composition tends to be improved.

[0066] (hardening agent) The resin composition of the present invention may further contain a curing agent. The curing agent is not particularly limited, but for example, phenol resin, acid anhydride having aromatic skeleton or alicyclic skeleton, water additive of said acid anhydride, and modified product of said acid anhydride are preferable. By using these preferable curing agents, it tends to be possible to obtain a resin cured product having excellent balance of heat resistance, moisture resistance, and electrical properties. Only one type of curing agent may be used, or two or more types may be used in combination.

[0067] The phenolic resin used as the curing agent is not particularly limited. Specific examples of the phenolic resin include phenolic novolac, o-cresol novolac, p-cresol novolac, t-butylphenol novolac, dicyclopentadiene cresol, polyparavinylphenol, bisphenol A type novolac, xylylene modified novolac, decalin modified novolac, poly(di-o-hydroxyphenyl)methane, poly(di-m-hydroxyphenyl)methane, poly(di-p-hydroxyphenyl)methane, etc. Among them, in order to further improve the flexibility and flame retardancy of the resin composition and to improve the mechanical properties and heat resistance of the resin cured product, novolac type phenolic resins having a rigid main chain skeleton; phenolic resins having a triazine skeleton; are preferred. In addition, in order to improve the flexibility of the resin composition and the toughness of the resin cured product, phenolic resins having an allyl group are preferred.

[0068] Commercially available phenolic resins include MEH-8005, MEH-8000H, and NEH-8015 manufactured by Meiwa Chemical Industry Co., Ltd.; YLH903 manufactured by Mitsubishi Chemical Corporation; LA-7052, LA-7054, LA-7751, LA-1356, and LA-3018-50P manufactured by Dainippon Ink Co., Ltd.; and PSM6200, PS6313, and PS6492 manufactured by Gun-ei Chemical Industry Co., Ltd.

[0069] The acid anhydride having an aromatic skeleton, the water additive of the acid anhydride, and the modified product of the acid anhydride used as the curing agent are not particularly limited.Specific examples include SMA resin EF30 and SMA resin EF60 manufactured by Sartomer Japan Co., Ltd.; ODPA-M and PEPA manufactured by Manac Co., Ltd.; Ricadit MTA-10, Ricadit TMTA, Ricadit TMEG-200, Ricadit TMEG-500, Ricadit TMEG-S, Ricadit TH, Ricadit MH-700, Ricadit MT-500, Ricadit DSDA, and Ricadit TDA-100 manufactured by New Japan Chemical Co., Ltd.; and EPICLON B4400 and EPICLON B570 manufactured by Dainippon Ink and Chemicals Co., Ltd.

[0070] The acid anhydride having alicyclic skeleton, the water addition product of said acid anhydride, and the modified product of said acid anhydride are preferably the acid anhydride having polyalicyclic skeleton, the water addition product of said acid anhydride, the modified product of said acid anhydride, the acid anhydride having alicyclic skeleton obtained by addition reaction of terpene compound and maleic anhydride, the water addition product of said acid anhydride, and the modified product of said acid anhydride.Specific examples include Ricajit HNA and Ricajit HNA-100 manufactured by New Japan Chemical Co., Ltd.; Epicure YH306 and Epicure YH309 manufactured by Mitsubishi Chemical Corporation.

[0071] The curing agent is preferably contained in an amount of 0 to 70% by mass, and particularly preferably 0 to 55% by mass, based on 100% by mass of the resin composition excluding the inorganic filler and the solvent. When the content of the curing agent is equal to or more than the lower limit, sufficient curing performance can be obtained. When the content of the curing agent is equal to or less than the upper limit, the curing reaction proceeds effectively, the crosslinking density is improved, the strength is increased, and the film formability is further improved.

[0072] When the thermosetting resin is an epoxy resin, the content of reactive groups in the curing agent is not particularly limited, but may be 0 equivalents relative to the amount of epoxy groups in the thermosetting resin, and is preferably 0.05 equivalents or more, more preferably 0.1 equivalents or more, even more preferably 0.15 equivalents or more, and particularly preferably 0.2 equivalents or more. Also, it is preferably 2 equivalents or less, more preferably 0.9 equivalents or less, even more preferably 0.6 equivalents or less, and particularly preferably 0.4 equivalents or less relative to the amount of epoxy groups in the thermosetting resin. When the content of reactive groups in the curing agent relative to the amount of epoxy groups in the thermosetting resin is equal to or greater than the lower limit, the curing rate is prevented from decreasing, epoxy groups are less likely to remain, and the strength of the cured resin tends to be improved and the moisture absorption is suppressed. On the other hand, when the content is equal to or less than the upper limit, the elastic modulus of the cured resin tends to be high.

[0073] (Other Ingredients) The resin composition of the present invention may further contain other components in addition to the inorganic filler, the thermosetting resin, the thermosetting catalyst and the curing agent, within the range that does not impair the effects of the present invention. Examples of other components include surface treatment agents such as silane coupling agents which improve the interfacial adhesion strength between the resin composition and an inorganic filler which is sometimes used when producing a resin cured product using the resin composition; insulating carbon components such as reducing agents; viscosity adjusters; dispersants; thixotropy-imparting agents; flame retardants; colorants; organic solvents; and thermoplastic resins. Among these, when the resin composition further contains a dispersant, it becomes possible to form a uniform resin cured product, and the thermal conductivity and dielectric breakdown characteristics of the obtained resin cured product may be improved. Also, when the resin composition further contains a thermoplastic resin, it may be possible to impart appropriate elongation to the resin composition, relieve the generated stress, and suppress the generation of cracks in a temperature cycle test.

[0074] The dispersant preferably has a functional group containing hydrogen atoms having hydrogen bonding properties. When the dispersant has a functional group containing hydrogen atoms having hydrogen bonding properties, the thermal conductivity and dielectric breakdown properties of the cured resin can be further improved. Examples of the functional group containing hydrogen atoms having hydrogen bonding properties include a carboxyl group (pKa=4), a phosphate group (pKa=7), and a phenol group (pKa=10).

[0075] The pKa of the functional group containing a hydrogen atom having hydrogen bonding ability is preferably 2 to 10, more preferably 3 to 9. When the pKa is 2 or more, the acidity of the dispersant is in an appropriate range, and the reaction of the epoxy resin in the thermosetting resin component may be easily suppressed. Therefore, when the molded product in an uncured state is stored, the storage stability tends to be improved. When the pKa is 10 or less, the function as a dispersant is sufficiently performed, and the thermal conductivity and dielectric breakdown characteristics of the resin cured product tend to be sufficiently improved.

[0076] The functional group containing a hydrogen atom capable of forming a hydrogen bond is preferably a carboxyl group or a phosphate group, which can further improve the thermal conductivity and dielectric breakdown characteristics of the cured resin.

[0077] Specific examples of the dispersant include polyester-based carboxylic acids, polyether-based carboxylic acids, polyacrylic-based carboxylic acids, aliphatic carboxylic acids, polysiloxane-based carboxylic acids, polyester-based phosphoric acids, polyether-based phosphoric acids, polyacrylic-based phosphoric acids, aliphatic phosphoric acids, polysiloxane-based phosphoric acids, polyester-based phenols, polyether-based phenols, polyacrylic-based phenols, polysiloxane-based phenols, etc. The dispersant may be used alone or in combination of two or more kinds.

[0078] As the thermoplastic resin, any generally known thermoplastic resin can be used. Specific examples include vinyl polymers such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, (meth)acrylic resin, ethylene-vinyl acetate copolymer, and ethylene-vinyl alcohol copolymer; polyesters such as polylactic acid resin, polyethylene terephthalate, and polybutylene terephthalate; polyamides such as nylon and polyamidoamine; polyvinyl acetal resins such as polyvinyl acetoacetal, polyvinyl benzal, and polyvinyl butyral resin; ionomer resins, polyphenylene ether, polyphenylene sulfide, polycarbonate, polyether ether ketone, polyacetal, ABS resin, LCP (liquid crystal polymer), fluorine resin, urethane resin, silicone resin, and various elastomers. The thermoplastic resin may be a modified product of these exemplified resins.

[0079] These thermoplastic resins may be uniform in the resin phase of the resin cured product, or may be phase-separated and have a recognizable shape. In the case of phase-separated, the shape of the thermoplastic resin in the resin cured product may be particulate or fibrous. The thermoplastic resin may be contained as the organic filler described above. The inclusion of a thermoplastic resin may impart appropriate elongation to the resin composition, reduce generated stress, and suppress the occurrence of cracks during a temperature cycle test.

[0080] When the thermoplastic resin and the organic filler are insoluble in the thermosetting resin, the viscosity of the resin composition is prevented from increasing, and when the resin composition is molded into a sheet as described below, the smoothness of the sheet surface can be improved. In this case, by simultaneously mixing a thermoplastic resin and an organic filler that are insoluble in the thermosetting resin with a large amount of inorganic filler, the component phase that is thermoplastic and has good elongation can be efficiently dispersed in the cured resin, and stress can be easily relaxed. Therefore, it is possible to suppress the occurrence of cracks in the cured resin without reducing the elastic modulus of the cured resin. For these reasons, polyamide resins such as nylon, cellulose resins, etc. are preferred as the thermoplastic resin, and polyamide resins such as nylon are particularly preferred.

[0081] The resin composition of the present invention may further contain an optional organic solvent, for example, in order to improve the coatability when a sheet-like cured resin product is formed through a coating step.

[0082] Examples of organic solvents that may be contained in the resin composition of the present invention include methyl ethyl ketone, cyclohexanone, propylene glycol monomethyl ether acetate, butyl acetate, isobutyl acetate, propylene glycol monomethyl ether, etc. The organic solvents may be used alone or in combination of two or more.

[0083] When the resin composition of the present invention further contains an optional organic solvent, the content of the organic solvent is appropriately determined depending on the handleability of the resin composition when preparing a resin cured product, the shape before curing, drying conditions, etc. When the resin composition of the present invention is in a slurry state to be subjected to a coating step described later, it is preferable to use an organic solvent so that the solid content (total of components other than the solvent) concentration in the resin composition of the present invention or in the resin composition of the present invention after the addition of an inorganic filler described later is 10 to 90 mass%, particularly 40 to 80 mass%. Furthermore, when the resin composition of the present invention is in the form of a sheet that has been subjected to processes such as coating and drying, the organic solvent is preferably used so that the solids concentration (total of components other than the solvent) in the resin composition of the present invention or in the resin composition of the present invention after the addition of an inorganic filler described below is 95 mass % or more, and more preferably 98 mass % or more.

[0084] [Production of Resin Composition and Cured Resin] The method for producing the above-mentioned resin composition of the present invention and the cured resin product of the present invention will be described below by taking as an example a method for producing a sheet-like cured resin product made of the cured resin product of the present invention.

[0085] The sheet-shaped cured resin product can be produced by a commonly used method, for example, by preparing the resin composition of the present invention, forming the resin composition into a sheet, and curing the sheet.

[0086] The resin composition can be obtained by uniformly mixing the inorganic filler, the thermosetting resin, the thermosetting catalyst, and other components added as necessary by stirring and kneading. For the mixing, a general kneading device such as a mixer, a kneader, a single-screw kneader, or a twin-screw kneader can be used, and heating may be performed during mixing, if necessary.

[0087] The order of mixing each compounding component may be arbitrary as long as there are no particular problems such as the generation of reaction, precipitation, etc. For example, a method may be used in which a thermosetting resin component is mixed and dissolved in an organic solvent (e.g., methyl ethyl ketone) to prepare a resin liquid, an inorganic filler and other components that have been thoroughly mixed are added to the obtained resin liquid and mixed, and then an organic solvent is further added and mixed to adjust the viscosity, and additives such as a curing agent, a curing accelerator, and a dispersing agent are further added and mixed.

[0088] The prepared resin composition can be molded into a sheet and cured by any commonly used method. The resin composition in a slurry state can be molded into a sheet by a doctor blade method, a solvent casting method, an extrusion film forming method or the like. The solvent in the resin composition can be removed by a known heating method such as a hot plate, a hot air oven, an IR heating oven, a vacuum dryer, or a high-frequency heater.

[0089] An example of a method for producing a cured resin product using a slurry-like resin composition will now be described.

[0090] [Coating process] First, a coating film (sheet-shaped resin composition) is formed on the surface of a substrate by applying a slurry-like resin composition. Specifically, a coating film is formed on the substrate by a dip method, a spin coat method, a spray coat method, a blade method, or any other method using the slurry-like resin composition. A coating device such as a spin coater, a slit coater, a die coater, or a blade coater can be used to apply the slurry-like resin composition. By using the coating device, a coating film of any thickness can be uniformly formed on the substrate. As the substrate, copper foil or PET film, which will be described later, is generally used, but there is no particular limitation.

[0091] [Drying process] The coating film formed by applying the slurry resin composition is usually dried at a temperature of 10 to 150°C, preferably 25 to 120°C, and more preferably 30 to 110°C in order to remove the solvent and low molecular weight components. If the drying temperature is below the upper limit, the curing of the thermosetting resin in the slurry resin composition is suppressed, and the resin in the sheet-shaped resin composition tends to flow in the subsequent pressurizing step, making it easier to remove voids. If the drying temperature is above the lower limit, the solvent can be effectively removed, and productivity tends to improve.

[0092] The drying time is not particularly limited and can be appropriately adjusted depending on the state of the slurry resin composition, the drying environment, etc. The drying time is preferably 1 minute or more, more preferably 2 minutes or more, even more preferably 5 minutes or more, even more preferably 10 minutes or more, particularly preferably 20 minutes or more, and most preferably 30 minutes or more. On the other hand, the drying time is preferably 4 hours or less, more preferably 2 hours or less. When the drying time is equal to or longer than the lower limit, the solvent can be sufficiently removed, and the residual solvent tends to be prevented from forming voids in the cured resin. When the drying time is equal to or shorter than the upper limit, the productivity tends to be improved, and the production cost tends to be reduced.

[0093] [Pressure process] After the drying step, it is desirable to subject the obtained sheet-like resin composition to a pressurizing step for the purposes of bonding the inorganic fillers together to form heat paths, eliminating voids and gaps in the sheet, improving adhesion to the substrate, etc.

[0094] In the pressurizing step, the heating temperature of the sheet-like resin composition on the substrate is not particularly limited. The heating temperature is preferably 10°C or higher, more preferably 20°C or higher, and even more preferably 30°C or higher. The heating temperature is preferably 300°C or lower, and more preferably 250°C or lower. When the heating temperature is within the above-mentioned numerical range, the melt viscosity of the resin in the coating film can be reduced, and voids and gaps in the cured resin can be eliminated. In addition, when the heating temperature is below the above-mentioned upper limit, decomposition of organic components in the sheet-like resin composition and the cured resin, and voids caused by residual solvent tend to be suppressed.

[0095] The time of the pressurizing step is not particularly limited. The time of the pressurizing step is preferably 30 seconds or more, more preferably 1 minute or more, even more preferably 3 minutes or more, and particularly preferably 5 minutes or more. The time of the pressurizing step is preferably 1 hour or less, more preferably 30 minutes or less, and even more preferably 20 minutes or less. When the pressurizing time is equal to or less than the upper limit, the production time of the cured resin can be reduced, and the production cost tends to be reduced, whereas when the pressurizing time is equal to or more than the lower limit, the gaps and voids in the cured resin can be sufficiently removed, and the heat transfer performance and the voltage resistance characteristics tend to be improved.

[0096] [Curing process] The curing step for completely curing the resin composition of the present invention may be carried out under pressure or without pressure. Also, the pressurizing step and the curing step may be carried out simultaneously. The load when the pressurizing step and the curing step are performed simultaneously is not particularly limited. It is preferable to apply a load of 2 MPa or more to the sheet-shaped resin composition on the substrate, more preferably 5 MPa or more, and more preferably 9 MPa or more. In addition, the load is preferably 2000 MPa or less, more preferably 1500 MPa or less. When the load is equal to or less than the upper limit, the secondary particles of the inorganic filler are not destroyed, and a sheet having high thermal conductivity without voids in the sheet-shaped cured resin can be obtained. In addition, when the load is equal to or more than the lower limit, the contact between the inorganic fillers is good, and a thermal conduction path is easily formed, so that a cured resin having high thermal conductivity can be obtained.

[0097] When the pressing step and the curing step are performed simultaneously, the pressing time is not particularly limited. In this case, the pressing time is preferably 30 seconds or more, more preferably 1 minute or more, even more preferably 3 minutes or more, and particularly preferably 5 minutes or more. In addition, in this case, the pressing time is preferably 4 hours or less, more preferably 3 hours or less. When the pressing time is equal to or less than the upper limit, the manufacturing time of the sheet-shaped resin cured product can be suppressed, and the production cost tends to be reduced. On the other hand, when the pressing time is equal to or more than the lower limit, the gaps and voids in the sheet-shaped resin cured product can be sufficiently removed, and the heat transfer performance and the voltage resistance characteristics tend to be improved.

[0098] The heating temperature of the sheet-shaped resin composition on the substrate when the pressing step and the curing step are performed simultaneously is not particularly limited. The heating temperature is preferably 10°C or higher, more preferably 20°C or higher, and even more preferably 30°C or higher. The heating temperature is preferably 300°C or lower, and more preferably 250°C or lower. When the heating temperature is within the above numerical range, the melt viscosity of the resin in the coating film can be reduced, and voids and gaps in the cured resin can be eliminated. When the heating temperature is below the above upper limit, decomposition of organic components in the sheet-shaped resin composition and the cured resin sheet and voids caused by residual solvent tend to be suppressed.

[0099] When only the curing step is performed, the heating temperature of the sheet-like resin composition on the substrate is not particularly limited. In this case, the heating temperature is preferably 10°C or higher, more preferably 50°C or higher, and even more preferably 100°C or higher. In this case, the heating temperature is preferably 500°C or lower, more preferably 300°C or lower, and even more preferably 200°C or lower. When the heating temperature is within the above numerical range, the curing reaction of the resin is effectively promoted. Furthermore, when the heating temperature is within the above numerical range, thermal deterioration of the resin can be prevented. Furthermore, when the heating temperature is equal to or higher than the above lower limit, the curing reaction of the resin is effectively promoted.

[0100] The thickness of the cured resin is not particularly limited, but is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more. The thickness of the cured resin is preferably 400 μm or less, more preferably 300 μm or less. When the thickness of the cured resin is equal to or greater than the lower limit, the voltage resistance characteristics are obtained and the breakdown voltage tends to be improved. When the thickness of the cured resin is equal to or less than the upper limit, the device can be made smaller and thinner, and the thermal resistance of the cured resin (heat dissipation sheet) obtained tends to be suppressed.

[0101] <Composite molded body> The composite molded product of the present invention has the resin cured product of the present invention and a metal. For example, it is a laminate of a cured product part made of the resin cured product of the present invention and a metal part made of a metal. The metal part may be provided on only one surface of the cured product part made of the resin cured product of the present invention, or on two or more surfaces. For example, it may have a metal part on only one surface of the resin cured product, or it may have metal parts on both surfaces. In addition, the metal part may be patterned.

[0102] Such a composite molded product of the present invention can be produced by using a metal part as the substrate and forming the cured resin product of the present invention on the substrate according to the method described above. Alternatively, the composite molded product of the present invention can be produced by peeling a sheet-like resin composition or cured resin product formed on a substrate other than the metal part from the substrate, and then heat-pressing the sheet-like resin composition or cured resin product onto a metal member that will become the metal part.

[0103] In this case, the sheet-shaped resin composition or cured resin of the present invention is formed in the same manner as described above, except that it is applied to a substrate such as PET which may be treated with a release agent, and then the sheet-shaped resin composition or cured resin is peeled off from the substrate, and the sheet-shaped resin composition or cured resin is placed on another metal plate or sandwiched between two metal plates and pressurized to be integrated.

[0104] In this case, the metal plate may be a metal plate having a thickness of about 10 μm to 10 cm and made of copper, aluminum, nickel-plated metal, etc. The surface of the metal plate may be physically roughened or chemically treated with a surface treatment agent, etc. From the viewpoint of adhesion between the resin composition and the metal plate, it is more preferable that the surface of the metal plate is subjected to such treatment.

[0105] <Semiconductor devices> The semiconductor device of the present invention has the composite molded article of the present invention. The composite molded article of the present invention can be used as a semiconductor device. In particular, it can be usefully used in a power semiconductor device that can achieve high output and high density by operating at high temperatures. EXAMPLES

[0106] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. Various conditions and values ​​of evaluation results in the following examples indicate preferred ranges of the present invention, similar to the preferred ranges in the embodiments of the present invention, and the preferred ranges of the present invention can be determined by taking into consideration the preferred ranges in the above-mentioned embodiments and the values ​​in the following examples or the ranges indicated by a combination of values ​​between the examples.

[0107] <Ingredients> The raw materials used in the examples and comparative examples are as follows.

[0108] (thermosetting resin) Resin component 1: a bifunctional epoxy resin disclosed in Example 1 of JP 2006-176658 A Resin component 2: Bisphenol F type solid epoxy resin manufactured by Mitsubishi Chemical Corporation Polystyrene equivalent weight average molecular weight: 60,000 Resin component 3: Bisphenol A type liquid epoxy resin manufactured by Mitsubishi Chemical Corporation Resin component 4: Nagase ChemteX multifunctional epoxy resin containing a structure with four or more glycidyl groups per molecule Resin component 5: Hydrogenated bisphenol A type liquid epoxy resin manufactured by Mitsubishi Chemical Corporation Resin component 6: p-aminophenol type liquid epoxy resin manufactured by Mitsubishi Chemical Corporation Resin component 7: Biphenyl-type solid epoxy resin manufactured by Mitsubishi Chemical Corporation Resin component 8: Nagase ChemteX multifunctional epoxy resin containing a structure with three or more glycidyl groups per molecule

[0109] (Agglomerated inorganic filler) Inorganic filler 1: boron nitride agglomerated particles having a house-of-cards structure, produced in accordance with the method for producing boron nitride agglomerated particles disclosed in the examples of WO 2015 / 119198.

[0110] (Other fillers) Inorganic filler 2: Admatechs, spherical alumina particles New Mohs hardness: 9 Volume average particle size: 6.5 μm Thermal conductivity: 20~30W / m K

[0111] (hardening agent) Hardener 1: MEH-8000H manufactured by Meiwa Kasei Co., Ltd. MEH-8000H is a phenolic resin hardener.

[0112] (Thermosetting catalyst) Thermosetting curing catalyst 1: 2E4MZ-A manufactured by Shikoku Kasei Corporation. 2E4MZ-A corresponds to 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(17')]-ethyl-s-triazine, and has both a structure derived from imidazole and a structure derived from triazine in one molecule. Molecular weight of 2E4MZ-A: 247 Properties of 2E4MZ-A: Solid Melting point of 2E4MZ-A: 215~225℃ Solubility of 2E4MZ-A in DMF: 10% by mass or less

[0113] Thermosetting curing catalyst 2: 2PHZ-PW manufactured by Shikoku Kasei Corporation. 2PHZ-PW is 2-phenyl-4,5-dihydroxymethylimidazole. Molecular weight of 2PHZ-PW: 204 Properties of 2PHZ-PW: Solid Melting point of 2PHZ-PW: 230℃ or higher (decomposes at 230℃) 2Average particle size of PHZ-PW: approx. 3 μm Solubility of 2PHZ-PW in DMF: 10% by mass or less

[0114] Thermosetting curing catalyst 3: C11Z-CN manufactured by Shikoku Kasei Corporation. C11Z-CN is 1-cyanoethyl-2-undecylimidazole. Molecular weight of C11Z-CN: 275 Properties of C11Z-CN: Solid Melting point of C11Z-CN: 47-52℃ Solubility of C11Z-CN in DMF: greater than 10% by mass

[0115] Thermosetting catalyst 4: 2MAOK-PW manufactured by Shikoku Kasei Co., Ltd. 2MAOK-PW is 2,4 diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct. Molecular weight of 2MAOK-PW: 384 2MAOK-PW Properties: Solid 2Melting point of MAOK-PW: 260℃ or higher (decomposition at 260℃) 2MAOK-PW average particle size: approx. 2um 2Solubility of MAOK-PW in DMF: 10% by mass or less

[0116] <Example 1> Using a planetary stirring device, a mixture was prepared with resin component 1, resin component 4, resin component 7, curing agent 1, curing catalyst 1, curing catalyst 2, inorganic filler 1, and inorganic filler 2, as shown in Table 1 below. When preparing the mixture, 18.6% by mass each of methyl ethyl ketone and cyclohexanone were used as solvents so that the mixture accounted for 62.8% by mass (solid content concentration) of the coating slurry.

[0117] The obtained slurry-like resin composition was applied to a PET substrate by a doctor blade method, and then heated and dried at 60° C. for 120 minutes, followed by pressing to obtain a sheet-like resin composition having a thickness of 150 μm. The total content of methyl ethyl ketone and cyclohexanone in the sheet-like resin composition was 1 mass% or less.

[0118] (Preparation of cured resin for measuring thermal conductivity) The sheet-shaped resin composition was sandwiched between PET and pressed at 120°C and 9 MPa for 20 minutes to obtain a cured resin material for measuring thermal conductivity. In addition, four types of cured resin materials with different thicknesses were obtained by pressing two, three, and four sheets of the sheet-shaped resin composition in a stacked state using the same method. These four types of cured resin materials with different thicknesses were used as the cured resin materials for measuring thermal conductivity.

[0119] (Preparation of composite molding for measuring peel strength ratio) The sheet-like resin composition was sandwiched between two 105 μm-thick copper plates, pressurized at 120° C. and 9 MPa for 30 minutes, then heated and pressurized at 175° C. and 9 MPa for 30 minutes to obtain a composite molded product for measuring the peel strength ratio. In order to secure a portion to be pulled during the peel test, one of the copper plates was made longer in the major axis direction than the sheet.

[0120] (Preparation of composite molded body for reflow test) A sheet-like resin composition was sandwiched between one copper plate of thickness 500 and one of 2,000 μm, whose surfaces had previously been roughened 100 times with a #120 file, and the plates were pressurized at 120°C and 9 MPa for 30 minutes.The plate was then heated and pressurized at 175°C and 9 MPa for 30 minutes to obtain a composite molded product for reflow testing. The composite molded body obtained above was etched by a prescribed method to pattern a 500 μm copper plate, so that two circular patterns of φ25 mm remained.

[0121] (Measurement of thermal conductivity) The thermal resistance of each of the cured resins used to measure thermal conductivity was measured using a Mentor Graphics T3ster DynTIM Tester. Thermal conductivity was calculated from the relationship between the film thickness of each of the four types of cured resins and the measured thermal resistance. The probe size during measurement was φ12.8mm, the fixing pressure was 3400kPa, and the measurement time was 300sec. Shin-Etsu Chemical's OIL COMPOUND (product name: G-747) was used to increase the adhesion between the sample and the probe.

[0122] (Measurement and evaluation of peel strength ratio) One side of the composite molded body was fixed to a jig, and a copper plate longer in the longitudinal direction than the sheet was pulled at 50 mm / min in a direction perpendicular to the fixed sample. From the resulting data, the average load in the stable region was calculated to calculate the peel strength a. Furthermore, the same sheet-like molded body was left at room temperature for one day before pressing, and then a composite molded body was produced in the same manner, measured, and the peel strength b was calculated, and the peel strength ratio of these two, = b / a, was calculated. The peel strengths were evaluated according to the following criteria. A: The peel strength ratio is 0.9 or more. B: The peel strength ratio is less than 0.9.

[0123] (Evaluation by reflow test) The composite molded body for the reflow test was stored in an environment of 85°C and 85% RH for 3 days using a thermohygrostat SH-221 (manufactured by Espec Corporation), and then heated from room temperature to 290°C in 12 minutes in a nitrogen atmosphere within 30 minutes, held at 290°C for 10 minutes, and then cooled to room temperature (moisture absorption reflow test). The interface between the copper plate and the cured resin was then observed using an ultrasonic imaging device FineSAT (FS300III) (manufactured by Hitachi Power Solutions). The measurement was performed using a probe with a frequency of 50 MHz, a gain of 30 dB, and a pitch of 0.2 mm, and the sample was placed in water. Evaluation was based on the following criteria. A: No interfacial peeling is observed. B: Peeling was observed at the interface.

[0124] <Examples 2 and 3, Comparative Examples 1 to 4> A sheet-shaped resin composition was obtained in the same manner as in Example 1, except that the components were used so as to obtain the composition shown in Table 1. Then, a cured resin for measuring thermal conductivity, a composite molded product for measuring peel strength ratio, and a composite molded product for a reflow test were produced and evaluated.

[0125] The results for each example are shown in Table 1.

[0126] [Table 1]

[0127] The results of the examples show that the resin composition of the present invention contains multiple thermosetting catalysts, which results in a high thermal conductivity of the resulting cured resin. It also shows that the storage stability of the resin composition is improved, and the adhesion between metal and the cured resin is improved in a reflow test. [Industrial Applicability]

[0128] The resin composition of the present invention gives a cured product which has excellent thermal conductivity and adhesion to metals and is resistant to interfacial peeling when composited with a metal. The cured resin of the present invention has excellent thermal conductivity and adhesion to metals, and is resistant to interfacial peeling when combined with a metal. The composite molded product of the present invention has excellent thermal conductivity and adhesion between the cured resin and metal, and is resistant to interfacial peeling. The semiconductor device of the present invention has excellent heat dissipation properties and excellent adhesion between the cured resin and metal, and is resistant to interfacial peeling.

Claims

1. A resin composition comprising an inorganic filler, a thermosetting resin, a thermosetting catalyst, and a curing agent, The inorganic filler comprises an aggregated inorganic filler; the thermosetting resin comprises an epoxy resin; The epoxy resin includes a multifunctional epoxy resin having three or more oxirane rings per molecule, Contains two or more thermosetting catalysts having a melting point of 100°C or higher, Two or more of the thermosetting catalysts have a structure derived from imidazole, At least one of the thermosetting catalysts having a structure derived from imidazole further has a structure derived from triazine in one molecule, A resin composition comprising, as the curing agent, at least one member selected from the group consisting of a novolac-type phenolic resin, a phenolic resin having a triazine skeleton, and a phenolic resin having an allyl group.

2. A resin composition comprising an inorganic filler, a thermosetting resin, a thermosetting catalyst, and a curing agent, The inorganic filler comprises an aggregated inorganic filler; the thermosetting resin comprises an epoxy resin; The epoxy resin includes a multifunctional epoxy resin having three or more oxirane rings per molecule, Contains two or more thermosetting catalysts having a melting point of 100°C or higher, The solubility of the thermosetting catalyst in N,N-dimethylformamide at 25° C. is 10% by mass or less; At least one of the thermosetting catalysts has a structure derived from imidazole, At least one of the thermosetting catalysts having a structure derived from imidazole further has a structure derived from triazine in one molecule, A resin composition comprising, as the curing agent, at least one member selected from the group consisting of a novolac-type phenolic resin, a phenolic resin having a triazine skeleton, and a phenolic resin having an allyl group.

3. The resin composition according to claim 2 , wherein two or more of the thermosetting catalysts have a structure derived from imidazole.

4. The resin composition according to any one of claims 1 to 3, wherein the epoxy resin contains an epoxy resin having a mass average molecular weight of 10,000 or more.

5. The resin composition according to any one of claims 1 to 4, wherein the structure derived from triazine is a structure derived from 1,3,5-triazine.

6. The resin composition according to any one of claims 1 to 5, wherein the melting point of at least one of the thermosetting catalysts is 200°C or higher.

7. The resin composition optionally further comprises a solvent, The resin composition according to any one of claims 1 to 6, wherein the content of the thermosetting catalyst is 0.1 to 10 mass% relative to 100 mass% of the resin composition excluding the inorganic filler and the optionally contained solvent.

8. The resin composition of any one of claims 1 to 7, wherein the agglomerated inorganic filler comprises boron nitride agglomerated particles.

9. The resin composition according to any one of claims 1 to 8, further comprising alumina.

10. The resin composition according to any one of claims 1 to 9, wherein the aggregated inorganic filler is boron nitride aggregated particles having a house of cards structure.

11. The resin composition according to any one of claims 1 to 10, wherein a main component of the resin composition is an epoxy resin.

12. A cured resin product using the resin composition according to any one of claims 1 to 11.

13. A composite molded article comprising the cured resin according to claim 12 and a metal.

14. A semiconductor device comprising the composite compact of claim 13.

Citation Information

Patent Citations

  • Filler for semiconductor sealing resin

    JP1989115940A

  • Heat release resin sheet and device containing heat release resin sheet

    JP2017036415A

  • Heat release insulation sheet, and laminate structure having sheet cured article as insulation layer

    JP2019119883A

  • Resin material, method for producing resin material, and laminate

    WO2018235918A1